Resource use and cost of annual health checks in primary care for people with intellectual disabilities. Issue 3 (21st November 2018) - Panca, M.; Buszewicz, M.; Strydom, A.; Hassiotis, A.; Welch, C. A.; Hunter, R. M.
Abstract: Background: The annual health check (AHC) programme, as part of a Directed Enhanced Service, offers an incentive to general practitioners in England to conduct health checks for people with intellectual disabilities (IDs). The aim of this analysis was to estimate the impact on health care costs of AHCs in primary care to the National Health Service in England by comparing adults with ID who did or did not have AHCs using data obtained from The Health Improvement Network. Methods: Two hundred eight records of people with ID from The Health Improvement Network database were analysed. Baseline health care resource use was captured at the time the first AHC was recorded (i.e. index date), or the earliest date after 1 April 2008 for those without an AHC. We examined the volume of resource use and associated costs that occurred at the time AHCs were performed, as well as before and after the index date. We then estimated the impact of AHCs on health care costs. Results: The average cost of AHC was estimated at £142.57 (95%CI £135.41 to £149.74). Primary, community and secondary health care costs increased significantly after the index date in the no AHC group owing to higher increase in resource utilisation. Regression analysis showed that the expected health care cost for those who have an AHC is 56% higher than for those who did not have an AHC. Age and gender were also associated with increase in expected health care cost. Conclusion: The level of resource utilisation increased in both (AHC and no AHC) groups after the index date. Although the level of resource use before index date was lower in the no AHC group, it increased after the index date up to almost reaching the level of resource utilisation in the AHC group. Further research is needed to explore if the AHCs are effective in reducing health inequalities.